Report of special committee on constitutional amendments (Benj. P. Avery, state printer, 1861)
1861? Report of the Special Committee on the proposed amendments adopted by the California legislature as stated in "Senate Bill No. 20." After analysis of the bill and the records, the committee proposed some changes as well as a committee to see if such changes could be made in the Journal.